Children's restorative justice in an intergroup context. Issue 3 (20th March 2021) - Yang, Xin; Wu, Zhen; Dunham, Yarrow
Abstract: The present study investigated 3‐ to 6‐year‐old (total n  = 158) children's restoration behaviors both when they were second‐party victims (Experiment 1) and when they were third‐party bystanders (Experiment 2) of transgressions. We also explored how group membership (based on color preference) affects these behaviors. We found that children preferred restoration to punishment, and that they emphasized restorative justice not only for themselves, but also for others. Furthermore, when they were victims of transgressions, the tendency to choose restoration over punishment was stronger in older than younger children. Second‐party restoration behavior was influenced by group concerns in that children treated in‐group transgressors more leniently than out‐group and unaffiliated transgressors, but third‐party restoration behavior was not. Our research challenges the view that punishment is the standard response to transgressions and suggests that alternative options like restoration are sometimes preferred over punishment by young children.